A comparative study of ultrasonography versus anatomical landmark guided techniques for erector spinae plane block in unilateral inguinal hernia surgeries - Ritu Pauranik; Ravindra Semaliya; Aseem Sharma; Manish Banjare; Aradhna Chourasiya (Asian Journal of Medical Sciences, 2025)
Background: Hernia surgery can cause immense pain and discomfort postoperatively. Erector spinae plane block (ESPB) is a relatively new method of treating pain associated with various surgical procedures. EPSB can be administered under ultrasonography (USG) guidance or guided by anatomical landmarks. Aims and Objectives: To compare the efficacy of the USG-guided technique with the anatomical landmark-guided technique for ESPB in unilateral inguinal hernia surgeries for post-operative analgesia, number of doses of rescue analgesia, hemodynamic variations, side effects, and patient satisfaction. Materials and Methods: This prospective, randomized, and comparative study involving 84 patients aged 18–65 years belonging to the American Society of Anesthesiologists grade I and II and fulfilling the inclusion criteria were randomized into two groups. Group UESPB received USG-guided ESPB, and Group LESPB received landmark-guided ESPB followed by a subarachnoid block. Postoperatively, pain assessment was done using a Numerical Rating Scale (NRS) score, and time to first rescue analgesic and total analgesic requirements were recorded. Results: Group UESPB patients experienced significantly lower NRS scores at 2 h, 8 h, and 24 h (P<0.05) following surgery as compared to group LESPB. The mean time for request of the first rescue analgesic in Group UESPB was 11.80±3.84 h, and in Group LESPB was 9.80±2.01 h, and the difference was statistically significant (P=0.003). Total post-operative analgesic consumption in 24 h in group UESPB was 114.2±37.91, which was lower than that in group LESPB (137.5±28.28 mg, P=0.002). Conclusion: UESPB provides improved analgesia and reduced analgesic consumption in the post-operative period as compared to the landmark-guided technique.